Species Richness and Endemism of Zingiberaceae in Cinchona Forest Reserve, Lantapan, Bukidnon, Philippines - Jayme, John Austin Lennox Faro; Mendez, Noe Polo; Mendez, Rainear Auxtero; Somera, Daniel F; Mohagan, Alma B (Journal of Tropical Life Science, 2020)
This study was carried out to provide information on species richness and endemism of Zingiberaceae in Cinchona Forest Reserve, Kaatuan, Lantapan, Bukidnon, Philippines. Transect walks, opportunistic sampling and collection within the sampling quadrats were conducted along established forest trails to collect ginger species. A total of 11 species of Zingiberaceae were documented belonging to two subfamilies (Alpinioideae and Zingiberoideae) and three tribes (Alpinieae, Hedychieae, and Zingibereae). The species recorded include Adelmeria alpina Elmer, Alpinia haenkei C.Presl, A. rufa C.Presl, Etlingera fimbriobracteata (K.Schum.) R.M.Sm., E. pubimarginata (Elmer) A.D.Poulsen, Hedychium philippinense K.Schum., Hornstedtia conoidea Ridl., H. lophophora Ridl., Meistera muricarpa (Elmer) Å korniÄk. & M.F.Newman, Zingiber banahaoense Mood & Theilade, and Zingiber sp. Of these, H. philippinense is the only threatened species recorded. All species are endemic to the Philippines except for E. fimbriobracteata which is native to Borneo and Zingiber sp. which is unidentified to the species level. These species represent 41% of the total genera and 9% of the total species of Zingiberaceae in the Philippines. The high endemicity (82%) in the total collected species in this study and the presence of a threatened species in this area calls for protection and conservation by the stakeholders.